ANTIHYPERTENSIVE TREATMENT IN ELDERLY PATIENTS WITH DIHYDROPYRIDINE CALCIUM ANTAGONISTS - Y. A. Karpov; V. V. Buza (Рациональная фармакотерапия в кардиологии, 2016)
The proofs of necessity of active arterial hypertension (AH) treatment in elderly patients are given. Peculiarities of pathogenesis of AH in elderly patients, connected predominantly with loss of big arteries elasticity and reasoning widely spread of isolated systolic AH in these patients, are discussed. Advantages of dihydropyridine calcium antagonists (DPCA) for AH treatment in elderly patients are proved, safety of treatment with DPCA is discussed. Data of clinical studies is analyzed. Analysis of target levels of blood pressure for antihypertensive treatment in elderly hypertensive patients is made. As a conclusion DPCA are the medicines of choice for AH treatment in elderly patients.